Structure relaxation in thin filamentary germanium crystals - Ermakov, A.P.; Drozhzhin, A.I. (Functional Materials, 2004)
In filamentary germanium crystals previously strained by torsion, the shape and structure return associated with reverse motion of screw dislocations towards the sources thereof have been revealed under action of thermal field and elastic one generated only by a constant uniaxial tensile loading. A change in mechanisms controlling the dislocation mobility and the plastic straining in the microcrystal has been found.